Downregulation of Circular RNA PSEN1 ameliorates ferroptosis of the high glucose treated retinal pigment epithelial cells via miR-200b-3p/cofilin-2 axis. Issue 2 (20th December 2021) - Zhu, Zhaoliang; Duan, Peng; Song, Huping; Zhou, Rongle; Chen, Tao
ABSTRACT: Ferroptosis is a form of programmed cell death that participates in the progression of numerous diseases. Long noncoding RNAs (lncRNAs) are dysregulated in diabetic retinopathy (DR). However, the role of lncRNAs in DR-induced ferroptosis is unclear. Adult retinal pigment epithelial cell line-19 (ARPE19) cells were treated with a high concentration of glucose (high glucose, HG) to mimic DR in vitro . The intracellular contents of glutathione, malondialdehyde, and ferrous ions were analyzed using the corresponding kits. The MTT assay was performed to measure the cell survival rate, and cell death was determined using propidium iodide and terminal deoxynucleotidyl transferase dUTP nick end labeling staining assays. Western blotting was conducted to detect the protein levels of GPX4, SLC7A11, and TFR1. The targeting relationships were verified using luciferase reporter and RNA pull-down assays. circ-PSEN1 was upregulated in HG-treated ARPE19 cells and showed high resistance to RNase R and Act D. Inhibition of circ-PSEN1 in ARPE19 cells ameliorated the ferroptosis induced by HG was ameliorated, as evidenced by changes in the ferroptosis-related biomarkers/genes and decreased cell death. Subsequently, circ-PSEN1 acted as a sponge for miR-200b-3p. Inhibition of miR-200b-3p partially reversed the effects of circ-PSEN1 on ferroptosis. Furthermore, cofilin-2 ( CFL2 ) was the target gene of miR-200b-3p, and it abrogated the inhibitory effect of miR-200b-3p on ferroptosis. Taken together, the findings indicate that knockdown of circ-PSEN1 can mitigate ferroptosis of ARPE19 cells induced by HG via the miR-200b-3p/CFL2 axis.